Bilateral facial nerve palsy: a rare post-dengue fever complication - Ng, Kim Khim; Wei, Chao Loh; Abdul Rashid, Anna Misya’il; KhanKhan, Abdul Hanif Yusof; Baharin, Janudin; Ibrahim, Azliza; Inche Mat, Liyana Najwa; Wan Sulaiman, Wan Aliaa; Fan, Kee Hoo; Basri, Hamidon (Springer Nature, 2022)
Background : An adolescent with recent dengue infection was presented with sudden onset of bilateral facial nerve palsy. It was a rare presentation and posed as a diagnostic challenge to all physicians.